Head First HTML5 programming : building web apps with Javascript - Freeman, Eric; Robson, Elisabeth (Beijing ; Sebastopol, CA : O'Reilly, 2011)
HTML has been on a wild ride.sure,html started as a mere markup language,but more recently HTML's put on some major muscle.
Includes index.
ma 06/03/2018
Keywords: HTML (Document markup language); JavaScript (Computer program language); Internet programming; Web site development